The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1099/00221287-148-11-3715
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of mitochondrial energization driven by the ultradian clock in a continuous culture of Saccharomyces cerevisiae

Abstract: A continuous culture of Saccharomyces cerevisiae IFO 0233, growing with glucose as the major carbon and energy source, shows oscillations of respiration with a period of 48 min. Samples taken at maxima and minima indicate that (i) periodic changes do not occur as a result of carbon depletion, (ii) intrinsic differences in respiratory activity occur in washed organisms and (iii) a respiratory inhibitor accumulates during respiratory oscillations. Plasma membrane and inner mitochondrial membranes generate transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…During the reductive phase of the cycle transcript, abundance was enriched with transcripts responsible for respiration, mitochondrial biogenesis, and actin arrangement. This production was compatible with our previous observation that mitochondrial cristae oscillate between orthodox (oxidative phase) and a condensed (reductive phase) state during a respiratory cycle (11). From these data we estimate that the metabolite concentrations peak 100-150°(12-18 min) after the peak in transcriptional activation of the pathway.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…During the reductive phase of the cycle transcript, abundance was enriched with transcripts responsible for respiration, mitochondrial biogenesis, and actin arrangement. This production was compatible with our previous observation that mitochondrial cristae oscillate between orthodox (oxidative phase) and a condensed (reductive phase) state during a respiratory cycle (11). From these data we estimate that the metabolite concentrations peak 100-150°(12-18 min) after the peak in transcriptional activation of the pathway.…”
Section: Resultssupporting
confidence: 79%
“…5] for months (4)(5)(6). These dynamics result in the temporal separation of many essential cellular functions, including redox biochemistry (7,8), transcription (9,10), energetics (11), chromosome cycle (1), and mitochondrial function (5). Although respiration is always active, the cellular redox state cycles between an oxidative phase and reductive phase.…”
mentioning
confidence: 99%
“…2E and (18,19,32,35,41,44). As a consequence, protein diffusion in the mitochondrial matrix may be affected (39,56).…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that changes in mitochondrial metabolism influence mitochondrial shape and matrix configuration (2,18,19,32,41,44) and thus the exchange of metabolites across the inner mitochondrial membrane and diffusion of matrix constituents (32,44,56). Using confocal microscopy and fluorescence correlation spectroscopy (FCS) of human skin fibroblasts expressing enhanced yellow fluorescent protein (EYFP) in the mitochondrial matrix (mitoEYFP), we recently showed that chronic CI inhibition by rotenone increased mitochondrial length and degree of branching and decreased the fraction of moving mitochondria and their velocity (27,30).…”
mentioning
confidence: 99%
“…Oscillation has been shown to occur in extreme metabolic conditions such as ischemia or substance depression in different models such as isolated cardiac mitochondria (6,7), cardiac myocytes (21), neurons (19,28,29), and yeast (13)(14)(15)(16). It has also been known that dissolved oxygen has oscillation in yeast (22).…”
mentioning
confidence: 99%